POSITIVISME: REVOLUSI FILSAFAT DAN DAMPAKNYA PADA KAJIAN SOSIAL ISLAM - Sulaeman, Eman (STIT AL-AMIN KREO TANGERANG, 2024)
This study aims to explore the contributions and critiques of positivism in contemporary Islamic studies. A qualitative approach with a descriptive-analytical method is employed to analyze relevant literature, including key works in positivist philosophy and Islamic studies. Positivism, as a philosophical approach emphasizing the importance of empirical data and scientific methods, has provided a strong foundation for objective analyses of Islamic issues such as gender equality, social justice, and sustainable development. In the context of Islamic politics, this approach facilitates the analysis of Muslim voters' behavior based on data, while in social fiqh, positivism aids in designing inclusive and data-driven public policies. However, this study also highlights critiques from phenomenology and postmodernism, which argue that positivism often neglects subjective, spiritual, and transcendental dimensions that are central to Islamic teachings. To develop a more holistic Islamic study, integrating positivist approaches with normative-spiritual perspectives is necessary, ensuring that Islamic studies remain relevant, inclusive, and responsive to contemporary challenges